1996
DOI: 10.1007/bf00192313
|View full text |Cite
|
Sign up to set email alerts
|

The responses of central octavolateralis cells to moving sources

Abstract: Mechanosensory lateral line units recorded from the medulla (medial octavolateralis nucleus) and midbrain (torus semicircularis) of the bottom dwelling catfish Ancistrus sp. responded to water movements caused by an object that passed the fish laterally. In terms of peak spike rate or total number of spikes elicited responses increased with object speed and sometimes showed saturation (Figs. 7, 14). At sequentially greater distances the responses of most medullary lateral line units decayed with object distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…However, it became apparent that at least object direction can be coded because the broad correlation peak flipped from positive to negative and vice versa if object direction was altered. Interestingly, neurons in the torus semicircularis of the goldfish show only a directional sensitivity and no velocity sensitivity to a moving object (Müller et al, 1996). This is in accordance with our data and with the fact that the flow velocity changes rapidly if a moving object passes a fish.…”
Section: Moving Objectsupporting
confidence: 91%
See 1 more Smart Citation
“…However, it became apparent that at least object direction can be coded because the broad correlation peak flipped from positive to negative and vice versa if object direction was altered. Interestingly, neurons in the torus semicircularis of the goldfish show only a directional sensitivity and no velocity sensitivity to a moving object (Müller et al, 1996). This is in accordance with our data and with the fact that the flow velocity changes rapidly if a moving object passes a fish.…”
Section: Moving Objectsupporting
confidence: 91%
“…The fish was positioned just outside the orbit, tangential to its perimeter [cf. Müller et al (1996), their Fig. 1].…”
Section: Methodsmentioning
confidence: 99%
“…As distance increased, the response decayed as a power function of distance. Müller, Fleck & Bleckmann (1996) towed a rectangular object on a circular orbit at various speeds near a catfish and Mogdans & Bleckmann (1998) close to a goldfish, eliciting responses that increase with the speed of towing. The peripheral lateral line units of the goldfish responded with predictable patterns.…”
Section: Flow Reconstruction: Viscous Effectsmentioning
confidence: 99%
“…Moving object stimuli also revealed that certain central lateral line units are highly sensitive to the direction of object motion (Bleckmann and Zelick, 1993;Müller et al, 1996;Wojtenek et al, 1998).…”
mentioning
confidence: 99%